HUBUNGAN PERILAKU DAN KEJADIAN DEMAM BERDARAH DENGUE DI PUSKESMAS TIGO BALEH KECAMATAN AUR BIRUGO TIGO BALEH KOTA BUKITTINGGI TAHUN 2014 - Sulistiawan, Andika; Putra, Yuhendri (LPPM Universitas Prima Nusantara Bukittinggi, 2015)
Dengue feveris a disease caused by the dengue virus isclassified as an arbovirus and entered into the patient's body through the bite of Aedes aegypty. Based on the initial survey, the working area Talawi health center has the highest prevalence of DHF compared to other health centers. The purpose of this study was to identify factors that affect the incidence of dengue in the health centers of Talawi, Sawahlunto 2014. Analytic descriptive method of research methods with cross sectional design. The population is all the people who are in the health centers of Talawi, Sawahlunto samples to taling 98 respondent. Univariate data processing is done by editing, coding, precessing, dry and bivariate data analysis performed by computer using statistical test chi-square test at the 0.05 significance. From the results of this study showed no significant relationship between know The results showed 47 respondents (48.0%) have less knowledge, more than half of the 58 respondents (59.2%) had a negative attitude, more than half of the 52 respondents (53.1%) had no clean environment, and who have had DHF 44 respondents (44.9%). In conclusion, no significant association between knowledge of the incidence of DHF (p value = 0.048), no significant relationship between the attitude of the incidence of DHF (p value = 0.037), no significant relationship between the environment and the incidence of DHF (p value = 0.023) incidence of DHF. Educational institutions are expected to be used as baseline data for further research, as the empirical data for the development of nursing, and a clean environment are expected to have a sense of community is higher so as to have a positive attitude to the incidence of dengue. This requires cooperation between public health officials in an effort to prevent the occurrence of DHF